Anti-Asian racism related stigma, racial discrimination, and protective factors against stigma: a repeated cross-sectional survey among university students during the COVID-19 pandemic - Boden-Albala, Bernadette; Ding, Xueting; Ryan, Nessa; Goodman, Sara; Wing, Jeffrey; Runnerstrom, Miryha Gould; Gutierrez, Desiree; Gibbs, Brooke; Robb, John Michael; Drum, Emily (Frontiers in Public Health, 2023)
Background Since the onset of the COVID-19 pandemic in March 2020, reports of anti-Asian American or Pacific Islander (AAPI) hate have increased in the United States. Institutions of higher education provide a unique opportunity to examine COVID-19 related stigma and protective factors in AAPI young adults enrolled in college. Objective The goal of this research was to examine COVID-19 related stigma among a diverse college student population. We posited that AAPI students experience more racial discrimination, internalized stigma, and/or anticipated racial discrimination than other students. We also sought to identify protective behavioral factors against stigma. Methods This study includes data from a repeated cross-sectional survey that was administered among college students at a large public university in the United States in April (n = 1,359) and November 2020 (n = 1,196). All university enrolled students with an active email account were eligible to participate in the online survey, which included questions about COVID-19 stigma (anticipated, enacted, internalized), stigma resistance, sources of COVID-19 information, lifestyle behaviors, and sociodemographic information. Binary logistic regression models were utilized to assess differences in stigma between race and ethnic groups and to identify factors associated with stigma. Results AAPI students were more likely to experience all three types of stigma compared to other race and ethnic groups. AAPI students in both waves were at least 2 times more likely to experience enacted stigma and 7.3 times more likely to experience anticipated stigma in the earlier wave compared to non-Hispanic White students. Students who had experienced enacted stigma were more likely to experience anticipated stigma, and those who experienced enacted and anticipated stigma were more likely to experience internalized stigma. Higher education level, living with neighbors/roommates, maintaining a healthy lifestyle, and thinking positively about oneself may act as protective factors against different types of stigma. Conclusion AAPI students have a greater risk of experiencing COVID-19 stigma compared to those from other race and ethnic groups. Universities should combat anti-AAPI sentiments and COVID-19 stigma and promote public health efforts to build resistance against the negative effects of stigma.